Web-based management of time-series raster data - Siwela, Blessing (Department of Computer Science, 2014)
Data discovery and data handling often presents serious challenges to organizations that manage huge archives of raster datasets such as those generated by satellite remote sensing. Satellite remote sensing produces a regular stream of raster datasets used in many applications including environmental and agricultural monitoring. This thesis presents a system architecture for the management of time-series GIS raster datasets. The architecture is then applied in a prototype implementation for a department that uses remote sensing data for agricultural monitoring. The architecture centres on three key components. The first is a metadatabase to hold metadata for the raster datasets, and an interface to manage the metadatabase and facilitate the search and discovery of raster metadata. The design of the metadatabase involved the examination of existing standards for geographic raster metadata and the determination of the metadata elements required for time-series raster data. The second component is an interactive tool for viewing the time-series raster data discovered via the metadatabase. The third component provides basic image analysis functionality typically required by users of time-series raster datasets. A prototype was implemented using open source software and following the Open Geospatial Consortium specifications for web map services (WMS) version 1.3.0. After implementation, an evaluation of the prototype was carried out by the target users from the RRSU (Regional Remote Sensing Unit) to assess the usability, the added value of the prototype and its impact on the work of the users. The evaluation showed that the prototype system was generally well received, since it allowed both the data managers and users of time-series datasets to save significant amounts of time in their work routines and it also offered some raster data analyses that are useful to a wider community of time-series raster data managers.